Peran Teknik Negosiasi dan Komunikasi Dalam Menjalankan Bisnis - Yulie Aisyah Binrany; Olivia Theresia Manurung; Christian Putra Tarigan; Lenti Susanna Saragih; Danny Ajar Baskoro (Student Scientific Creativity Journal, 2024)
Effective communication plays a central role in the success of modern business, especially in the context of establishing good relationships with stakeholders. The ability to communicate clearly, responsively and on time is crucial in building a positive image, increasing work efficiency and creating a harmonious and productive work environment. Evaluation of the success of conveying information through feedback is an important key in developing effective communication, which can be done through market research or consumer research to understand consumers' identities precisely and design more effective marketing strategies in the future.